Low-Carbon Energy Risk and Renewable Energy Development: Insigths from Method of Moments Quantile Regression - Kalandarov, Feruz; Makhmudov, Samariddin; Ibadullaev, Dilshad; Matniyozov, Murodjon; Nasretdinova, Farangis; Sabirov, Khamid; Bahodirov, Nu’monkhon (International Journal of Energy Economics and Policy, 2025)
The current work investigates the effect of low-carbon energy risk on renewable energy development for the first time in the literature. The annual data used in the work contains the sample of 137 countries. For the empirical estimations, Method of Moments Quantile Regression (MMQR) is applied, considering the heteroscedastic nature of the data and energy markets as well. The results provide valuable findings that a decrease in low- carbon energy risk leads to a rise in renewable energy across all the quantiles. Moreover, the results remain robust when the sample is divided into developed and developing countries, further validating theoretical linkage. Policymakers should consider the components of low-carbon energy risk in the decision-making process to enhance renewable energy development.